Trabalho a céu aberto e sua relação com a saúde dos trabalhadores: exposição ao calor e a radiação solar - Jelvis Santos Machado (2022)
A large part of agroforestry activities are carried out in the field, in the open, subject to weather conditions, exposure to heat and ultraviolet radiation (UV) and other stressful conditions. In Brazil, only the Globe Thermometer Wet Bulb Index (WGBT) is standardized for assessments of occupational exposure to heat and it does not take into account important and specific variables for the measurement of UV radiation, a factor that can cause fragility in the characterization of the agents. harmful environmental factors present in rural activities carried out in the open. The UV radiation region, although classified as non-ionizing and not recognized in Brazilian legislation, can cause skin cancer, premature aging, cataracts and burns. It should also be considered that UV radiation can vary in its intensity depending on several factors such as latitude, altitude, local surface reflection (albedo), cloud cover, among other factors that are not always directly related to temperature or temperature. local thermal sensation. Thus, this study aimed to evaluate, in different Brazilian and Latin regions, the existence of a correlation between the WGBT and the Ultraviolet Index (UVI), as well as the applicability of these indices to determine the risk of developing occupational disorders related to these physical agents. in rural workers who develop their work activities in the open. In order to encompass the greatest possible variation in latitude, altitude and climate between the sampling points, data from five regions located in Brazil and two other located in South American countries were used. For each of the sampled regions, using regression equations, the mean values of WGBT and UVI were estimated, based on the following meteorological data: air temperature, water vapor pressure, relative humidity and global solar radiation. The results showed that there was no correlation between the WGBT and the UVI, the first being an index well correlated with the local temperature, while the second had a greater correlation with the local radiation, corroborating the fact that, locations that present temperatures below the limits of occupational exposure tolerance, according to the WGBT, may present conditions that expose workers to the risks of insalubrity resulting from exposure to UV radiation. It is concluded that the WGBT and UVI indices are indices with different applicability, being the WGBT appropriate for the characterization of occupational exposure to heat and the IUV more effective to characterize the exposure to UV radiation, both being together important tools for the proposition of preventive measures capable of preventing agroforestry workers from becoming ill due to exposure to heat and UV radiation.